Management of Idiopathic Scrotal Hydrocele in a Pomeranian Dog - Parmar, JJ; Parray, AH; Rao, Neha; Shah, AL; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A hydrocele is a collection of fluid within the tunica or processus vaginalis, and mostly it is congenital in youngand secondary in adults (Hsu et al., 2004).